Strategi Transformasi Pelayanan Publik Berbasis Big Data : Studi Kasus Pemerintah Kota Pekanbaru - Zahra Aqilah Dytihana; Aji Bayu Ramadhan; Arif Abdul Rahman Sakhi; Alwan Syarofi; Mohammad Rezza Fahlevvi; Ari Apriyansa (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Big Data can help public services change and improve faster by using digital tools. Digital tools can make public services better and faster by using Big Data. Public services can change and improve faster by using digital tools that use Big Data. Pekanbaru City uses data to make decisions and improve its services. The Big Data-based SIPENDUDUK application is already circulating to help people access information. Then there is a different system with the implementation of SPBE. There is one website where people can find the data they need. This literature study analyses how the Pekanbaru City government uses Big Data to transform its public services. The TOE framework approach is used, which has three parts: technology, organization, and environment. This study found that using information technology, such as population, helps speed up administrative services. SPBE creates a framework that allows data to be combined across sectors. Other feature portals such as Satu Data make data more accessible and transparent across sectors. These three innovations serve as the basis for integrating Big Data into public services. The final result of this study shows that the success of digital transformation in this region depends on more than just technology. It also depends on how ready the organization is and how much support they get from regulators. The possibility of Technology Organization Environment (TOE) public services working well is because they use three dimensional integration. This means that the Pekanbaru City government considers the needs of the community, the resources they have, and the changes they face.